Compensation strategy as a job satisfaction tool (GEON Journal (Management, Organizations and Business), 2019)
In the labor relationship between the company and the collaborator are the compensations (salaries, increases, incentives and Social Benefits) the calls to significantly influence the satisfaction of the employees, that is why organizations must establish strategic elements, then convert them to operational plans with a defined budget, knowing the collaborator not only in their personal matters, but also in family matters, their preferences, their tastes, their life project, understanding the integrality of being in contribution to the organization.
Keywords: Compesation; Job Satisfaction; Salaries; Job welfare